2017
DOI: 10.18632/oncotarget.22329
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variations inTERCandTERTgenes are associated with lung cancer risk in a Chinese Han population

Abstract: The study was aimed to explore whether the TERT and TERC polymorphisms are associated with the lung cancer risk. Five TERC and TERT polymorphisms were genotyped from 554 lung cancer patients and 603 healthy controls. We used χ2 test, genetic model, linkage disequilibrium (LD) and haplotype analyses to evaluate the association between the polymorphisms and lung cancer risk. We found that the allele “C” of rs10936599 (TERC) and the allele “T” of rs10069690 (TERT) were associated with increased risk of lung cance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 31 publications
1
11
0
Order By: Relevance
“…The characteristics of selected studies are summarized in Table. The 45 studies included nine on breast cancer (Garcia‐Closas et al, ; Haiman et al, ; Huo et al, ; Michailidou et al, , ; Palmer et al, ; Purrington et al, ) and, six on ovarian cancer (Bojesen et al, ; Earp et al, ; Kuchenbaecker et al, ; Lee et al, ; Phelan et al, ; Terry et al, ); five on lung cancer (Gao et al, ; Landi et al, ; Wang et al, ; Ye et al, ; Zhao et al, ). two each on glioma (Melin et al, ; Zhao et al, ), thyroid cancer (Gong et al, ; Gudmundsson et al, ), pancreatic cancer (Campa, Rizzato, et al, ; Petersen et al, ), prostate cancer (Panagiotou et al, ; Schumacher et al, ), colorectal cancer (Li et al, ; Pellatt, Wolff, Herrick, Lundgreen, & Slattery, ), RCC (Martino et al, ; Wu, Yan, et al, ), and leukemia (Sheng et al, ; Speedy et al, ); and one each on endometrial cancer (Prescott, McGrath, Lee, Buring, & De Vivo, ), bladder cancer (Rothman et al, ), testicular germ cell tumor (TGCTs) (Schumacher et al, ), melanoma (Llorca‐Cardenosa et al, ), multiple myeloma (Campa, Martino, et al, ), gastrointestinal stromal tumors (GISTs) (Zhang et al, ), non‐Hodgkin's lymphoma (NHL), diffuse Large B‐cell lymphoma (DLBCL), small lymphocytic lymphoma/chronic lymphocytic leukemia (SLL/CLL) (Shadrina et al, ), nasopharyngeal carcinoma (NPC) (Zhang et al, ), gastric cancer (Duan et al, ), esophageal cancer (Wu, Yan, et al, ), gastric cardia adenocarcinoma (GCA) (Zhang et al, ), hepatocellular carcinoma (HCC) (Zhang et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…The characteristics of selected studies are summarized in Table. The 45 studies included nine on breast cancer (Garcia‐Closas et al, ; Haiman et al, ; Huo et al, ; Michailidou et al, , ; Palmer et al, ; Purrington et al, ) and, six on ovarian cancer (Bojesen et al, ; Earp et al, ; Kuchenbaecker et al, ; Lee et al, ; Phelan et al, ; Terry et al, ); five on lung cancer (Gao et al, ; Landi et al, ; Wang et al, ; Ye et al, ; Zhao et al, ). two each on glioma (Melin et al, ; Zhao et al, ), thyroid cancer (Gong et al, ; Gudmundsson et al, ), pancreatic cancer (Campa, Rizzato, et al, ; Petersen et al, ), prostate cancer (Panagiotou et al, ; Schumacher et al, ), colorectal cancer (Li et al, ; Pellatt, Wolff, Herrick, Lundgreen, & Slattery, ), RCC (Martino et al, ; Wu, Yan, et al, ), and leukemia (Sheng et al, ; Speedy et al, ); and one each on endometrial cancer (Prescott, McGrath, Lee, Buring, & De Vivo, ), bladder cancer (Rothman et al, ), testicular germ cell tumor (TGCTs) (Schumacher et al, ), melanoma (Llorca‐Cardenosa et al, ), multiple myeloma (Campa, Martino, et al, ), gastrointestinal stromal tumors (GISTs) (Zhang et al, ), non‐Hodgkin's lymphoma (NHL), diffuse Large B‐cell lymphoma (DLBCL), small lymphocytic lymphoma/chronic lymphocytic leukemia (SLL/CLL) (Shadrina et al, ), nasopharyngeal carcinoma (NPC) (Zhang et al, ), gastric cancer (Duan et al, ), esophageal cancer (Wu, Yan, et al, ), gastric cardia adenocarcinoma (GCA) (Zhang et al, ), hepatocellular carcinoma (HCC) (Zhang et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…Accordingly, they might also explain the co-occurrence of both diseases. Furthermore, the germline variant, rs2736100, has been reported to be associated with lung ADC risk [205], and other TERT , TERC , OFBC1 , and RTEL1 polymorphisms have also been revealed as risk factors of LC [206,207]. However, telomere functionality and its contribution to LC development is controversial.…”
Section: Genetic and Epigenetic Alterations In Lung Cancer Associamentioning
confidence: 99%
“…By analyzing three lung cancer cell lines, a study demonstrated the binding of CTCF TF to one of the enhancer regions of TERT gene is responsible for TERT up-regulation [112]. Some genetic variants of TERC (rs10936599) or TERT (rs10069690, rs2242652 or rs2853677) are related with an increased lung cancer risk [113].…”
Section: Telomerase Rna Componentmentioning
confidence: 99%